Russische Literatur von der Mitte des 17. Jahrhunderts bis A. S. Puschkin (1650-1825) Literatur einer werdenden Nation. Ein Lesebuch - Schmidt, Horst (Sagners Slavistische Sammlung, 1998)
The progressive development of literature from the middle of the 17th century to A. S. Pushkin is essentially determined by the sections of the political and intellectual history of Russia. The poet personalities featured in this volume are each classified in the period in which the main weight of their action lies. In the selection of texts balanced all genres, including journalistic and literary theoretical, were considered, depending on the relevance of the works for the process of progressive enlightenment and bourgeois (feudalism and absolutism criticism, human rights, humanism and other bourgeois ideals) as well as for the artistic Mature of Russian literature.